User expectancies for green products: A case study on the internal customers of a social enterprise. Issue 3 (7th November 2016) - Lin, Chen-Ju; Chen, Hwang-Yeh
Abstract : Purpose: This study was commissioned by DA-AI Technology Co. Ltd. and used the outcome expectancy theory from the social cognitive framework and concept of planned behavior to structure an outside-inside user expectancy model. The purpose of this study is to identify the elements that influence internal customers to select green products. Design/methodology/approach: The model reflected the outside expectancy of users regarding three aspects: perceived benefits, barriers and perceived corresponding value of green products as the stimulus of a user-perceptive process. The trained onsite interviewers collected 438 completed questionnaires focused on the volunteers of Tzu Chi as the main subjects of this study. Findings: The volunteers emphasized the meaningfulness and superiority of products much more than they emphasized the enterprise image and brand image when they were trying to adopt green products. The volunteers did not express an unwillingness to adopt green products, even if they had to face the complexity of the products and pay an extra learning cost. Originality/value: The volunteers would decrease the consumption of green products when the price was high and would increase their consumption when their ecological values encouraged them to do so. This consumptive value implies that green product adoption was perceived to enhance the social image, self-assessed value and bodily happiness of the users because their inside expectancies were fulfilled.